X-factors in straight punches - Tong-lam, R.; Lawsirirat, C. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Straight punches are proven to be one of the most effective punches in Wing especially when boxers aim for far-reaching targets. Powerful straight punches require boxers to produce a series of force transfers from lower limbs to fists. Mechanically, the forces created from the lower limbs are approximately perpendicular to the forces created by fists. Hence, the forces from fists may not be derived from forms created from lower limbs as traditionally believed. This paper attempted to find the kinetic link of force transfer from lower limbs to fists. Three elite boxers were recruited in this study. Six high speed camera and two force platforms were used to collect data and 3D analysis was performed. The results showed that an X-factor contributed to the acceleration of straight punches resulted in the force of a straight punch.